Advanced Control Systems for Electric Drives - Merabet, Adel (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book provides extensive information about advanced control techniques in electric drives. Multiple control and estimation methods are studied for position and speed tracking in different drives. Artificial intelligence tools, such as fuzzy logic and neural networks, are used for specific applications using electric drives.